Find the gradient of the function f(x,y)=x^3 + y^3 -3xy at the point (2,1), given that f(2,1) = 6.

Firstly, establish that the correct method to do this is via differentiation: specifically implicit differentiation. To find the gradient, we need to find dy/dx. The differential with respect to x of x3 = 3x2. The differential with respect to x of y3 = 3y2dy/dx. The differential with respect to x of -3xy = -3y - 3xdy/dx (By Chain Rule - u = -3x v = y.) The differential with respect to x of 6 = 0. As such, we can form the equation: 0 = 3x2 + 3y2dy/dx - 3y - 3xdy/dx. Which can be rearranged to give dy/dx = (3x2 - 3y)/(3y2 - 3x). Subbing in our values for x and y, we get dy/dx = (322 - 31)/(312 - 32) = (12 - 3)/(3 - 6) = 9/-3 = -3. Thus our solution is -3.

Answered by Daniel D. Maths tutor

5054 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Find the turning points on the curve with the equation y=x^4-12x^2


Using the substitution x = 2cosu, find the integral of dx/((x^2)(4-x^2)^1/2), evaluated between x=1 and x=sqrt(2).


For a curve of gradient dy/dx = (2/(x^2))-x/4, determine a) d^2y/dx^2 b) the stationary point where y=5/2 c) whether this is a maximum or minmum point and d) the equation of the curve


Use the addition formulas: sin(x+y)=sin(x)*cos(y)+sin(y)*cos(x), cos(x+y)=cos(x)*cos(y)-sin(x)*sin(y) to derive sin(2x), cos(2x), sin(x)+sin(y).


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences